2023
DOI: 10.1111/ctr.14951
|View full text |Cite
|
Sign up to set email alerts
|

The utility of machine learning for predicting donor discard in abdominal transplantation

Abstract: Background Increasing access and better allocation of organs in the field of transplantation is a critical problem in clinical care. Limitations exist in accurately predicting allograft discard. Potential exists for machine learning to provide a balanced assessment of the potential for an organ to be used in a transplantation procedure. Methods We accessed and utilized all available deceased donor United Network for Organ Sharing data from 1987 to 2020. With these data, we evaluated the performance of multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Other researchers have concentrated on predicting allograft or donor discards. Pettit et al [57] showed the efficacy of the XGBoost model at predicting organ use, while Barah et al [58] observed random forest's proficiency in identifying kidneys at risk of discard, with Price et al [59] having developed a kidney discard risk index, identifying 21 factors predictive of organ discard.…”
Section: Addressing the Organ Shortagementioning
confidence: 99%
“…Other researchers have concentrated on predicting allograft or donor discards. Pettit et al [57] showed the efficacy of the XGBoost model at predicting organ use, while Barah et al [58] observed random forest's proficiency in identifying kidneys at risk of discard, with Price et al [59] having developed a kidney discard risk index, identifying 21 factors predictive of organ discard.…”
Section: Addressing the Organ Shortagementioning
confidence: 99%
“…3 ML has been used for LTx to evaluate graft survival and donor discard rates, however the varying results could be attributed to model selection or testing procedures. 4,5 In order to implement ML algorithms that predict post-LTx out-…”
Section: Introductionmentioning
confidence: 99%
“…Quantifying the risks associated with recipient‐donor matching becomes a paramount priority in ensuring proper transplantation practices. When assessing the risk associated with a specific donor‐recipient pair, there exists a multitude of donor and recipient variables that could potentially be considered 3–6 . Developing methods that enable more precise prediction of graft survival following LTx can enhance physician decision‐making, improving organ utilization and graft outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation